The impact of sensory marketing on customer loyalty in private sports clubs: Using perceived value as the mediating variable - Soleimani, M.; Ahmadi, S.; Akbar Zohrehvand, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
The purpose of this research was to investigate the effect of sensory marketing on customer loyalty of private sports clubs, with the mediating role of perceived value. The sample was composed of 385 people (18 to 65 years old) who attended private sports clubs in Tehran in 2019. The three instruments used were: Sensory Marketing Questionnaire, Perceived Value Questionnaire, Behavioral and Attitudinal Loyalty Questionnaire. The data analysis showed that sensory marketing through perceived value can be effective in the behavioral and attitudinal loyalty of customers of private fitness clubs. Therefore, the managers of sports clubs should go beyond measuring customer satisfaction and the quality of services provided and focus on customer loyalty, because the key to attract and retain customers is to improve their positive attitude towards sports service providers.